1986
DOI: 10.1111/j.1532-5415.1986.tb04240.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Depression and Cognitive Impairment After Hip Fracture

Abstract: Fifty patients, over 60 years of age, were evaluated for mental status change at the time of hip fracture. Specifically, demographic and historical data were gathered and patients were given an assessment battery to evaluate depression and cognitive impairment during hospitalization for femoral fracture. Prevalence of depression was 28%, and cognitive impairment was present in 40% of the patients evaluated. Pre-fracture activities of daily living were estimated. These data provide the first systematically accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…This figure was in the middle of the prevalence range noted in other similar studies [2,9,19]. Prevalence of depression was highest in the oldest age group and in those with dementia regardless of the gender.…”
Section: Discussionsupporting
confidence: 54%
“…This figure was in the middle of the prevalence range noted in other similar studies [2,9,19]. Prevalence of depression was highest in the oldest age group and in those with dementia regardless of the gender.…”
Section: Discussionsupporting
confidence: 54%
“…The study found that 14.3%, or one of every seven patients, developed MDD after hip fracture. This number is lower than the cross‐sectional prevalence of MDD in other studies of hip fracture 23 or other disabling medical events such as stroke 30 . The reason for the discrepancy is unknown but may reflect increasing prescription of antidepressants in older people or the exclusion of severely cognitively impaired patients.…”
Section: Discussionmentioning
confidence: 58%
“…The computerized case designation (AGECAT) showed an acceptable concordance with clinical diagnoses (kappa value for dementia 0.59, for depression 0.58). Some issues related to the high prevalence of major depression are discussed.KEY WoRDs-Elderly, medically ill, psychogeriatrics, AGECAT, GMS.Reports on the prevalence of psychiatric disorders (mainly dementia and depression) in elderly patients with medical illness are relatively scanty and prevalence rates are very varied (though generally high), ranging from 28% (Billig et al, 1986) to 42.1% (Magni et al, 1985). A large part of the variance is probably accounted for by differences in the target sample (age, type of medical illness), in methodology (questionnaire, semistructured interviews) and in the criteria for diagnosis (cut-off points, ICD-9, DSM-111, etc).…”
mentioning
confidence: 99%